INOVASI PELAYANAN PUBIK MELALUI PROGRAM SILASIMEDI DALAM UPAYA MENINGKATKAN PELAYANAN MASYARAKAT DI BIDANG CAPIL DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Azzahra, Shinta (LPPM UNSAP & FISIP UNSAP, 2025)
This research aims to determine how public service innovation occurs through the silasimedi program in efforts to improve community services in the field of civil registration at the Population and Civil Registration Office of Sumedang Regency, what factors hinder it, and how to address these obstacles. This research uses a qualitative method with descriptive analysis. Informants were selected using purposive sampling technique, including the Secretary of the Office, the Head of the Civil Registration Division, Civil Registration Staff, and Silasimedi Service Staff. Data collection techniques were carried out through literature study, field study (observation, interviews, and documentation), and triangulation. Subsequently, data processing used data collection, data reduction, data display, and conclusion or verification. The research results conclude that public service innovation through the silasimedi program in an effort to improve community services in the field of population and civil registration at the Sumedang Regency Population and Civil Registration Office has been going quite well. This can be seen from the innovations in products or services, processes, methods, strategies, and systems in its service innovation. There are several obstacles to the silasimedi service innovation, namely the lack of facilities and infrastructure, barriers in network accessibility and distance in outreach services, lack of public awareness about the importance of population documents, insufficient number of staff, and lack of employee training. Meanwhile, efforts are being made to add computer facilities and infrastructure, as well as socialization for the community about the importance of having population documents, and organizing internal training for employees. Based on the results of this study, it is suggested to add the number of employees during service as there is often a shortage in terms of human resources, as well as socialization in various media, such as social media and also directly to the public.